Effects of Microstructure Modification on Properties of AlN/BN Composites - 李美娟 张联盟 SHEN qiang ZHANG Dongming (Journal of Wuhan University of Technology. Materials science edition, 2008)
It is very difficult to prepare full-densified aluminum nitride-boron nitride （AIN/BN） composite ceramics with homogeneous microstructure and high thermal conductivity. Spark plasma sintering （SPS） was used to fully densify the AIN/BN composites in this work. Microstructure, mechanical properties and thermal conductivity of the SPS sintered AIN/BN composites with 5-30 vol% BN were investigated. The results show that the microstructure of composites is fine and homogenous, and the AIN/BN composites exhibit high mechanical properties. To promote the growth of AIN grains and modify the distribution of grain boundary in AIN/BN composites, a heat treating methodology was introduced through gas pressure sintering （GPS）. This processing was significantly beneficial to enhancing the thermal conductivity of the specimen. The thermal conductivity of AIN/BN composites with 5-30 vol% BN reached 60 W/m K after the samples were treated by GPS.